Taken from the Paradise Isle: the Hoshida family story, 1912-1945 - Hoshida, George, author; Hoshida, Tamae, author; Kim, Heidi, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2015)
Crafted from George Hoshida's diary and memoir, as well as letters faithfully exchanged with his wife Tamae, Taken from the Paradise Isle is an intimate account of the anger, resignation, philosophy, optimism, and love with which the Hoshida family endured their separation and incarceration during World War II. George and Tamae Hoshida and their children were an American family of Japanese ancestry who lived in Hawai'i. In 1942, George was arrested as a 'potentially dangerous alien' and interned in a series of camps over the next two years. Meanwhile, forced to leave her handicapped eldest daughter behind in a nursing home in Hawai'i, Tamae and three daughters, including a newborn, were incarcerated at the Jerome Relocation Center in Arkansas. George and Tamae regularly exchanged letters during this time, and George maintained a diary including personal thoughts, watercolors, and sketches. In Taken from the Paradise Isle these sources are bolstered by extensive archival documents and editor Heidi Kim's historical contextualization, providing a new and important perspective on the tragedy of the incarceration as it affected Japanese American families in Hawai'i. This personal narrative of the Japanese American experience adds to the growing testimony of memoirs and oral histories that illuminate the emotional, psychological, physical, and economic toll suffered by Nikkei as the result of the violation of their civil rights during World War II.--Provided by publisher.
Keywords: Hoshida, George, 1907-1985 -- Family; Hoshida, Tamae, 1908- -- Correspondence; Hoshida, George, 1907-1985 -- Correspondence; Hoshida, George, 1907-1985 -- Diaries; Japanese Americans -- Hawaii -- Biography; Japanese Americans -- Evacuation and relocation, 1942-1945; Jerome Relocation Center (Ark.)